Impact of a university–school collaboration model on pre-service teacher leadership development - Sholpan Kolumbayeva; Marfuga Аbsatova; Shyngys Nurlanov; Aliya Kosshygulova; Aigul Nogayeva (Institute of Advanced Engineering and Science, 2026)
The purpose of this study was to examine the impact of an innovative university–school collaboration model on leadership development (LD), operationalized through leadership competencies (LCs), among pre-service teachers (PTs) enrolled in teacher education programs (TEPs), and to explore the relationship between LCs and teaching self-efficacy. Specifically, the study investigated whether participation in the university–school collaboration model led to statistically significant improvements in key LCs within the Kazakhstani teacher education context. A quantitative quasi-experimental pretest–posttest control group design was employed, involving 120 PTs from Abai Kazakh National Pedagogical University in Almaty, Kazakhstan. The findings indicate that participation in the university–school collaboration model was associated with significant improvements in LCs across multiple dimensions. In addition, strong positive relationships were observed between LCs and teaching self-efficacy, suggesting that leadership-oriented learning experiences support broader aspects of professional confidence among PTs. No subject-specific differences in LD outcomes were identified, indicating the discipline-general applicability of the model. Overall, the study provides empirical evidence supporting multidimensional LD through structured university–school collaboration. The findings extend existing research on teacher leadership and offer practical guidance for designing scalable, experiential leadership components within initial TEPs.